Scenarios for the Welsh government budget to 2025 - 26 - Benjamin Deaner; David Phillips (Institute for Fiscal Studies (IFS), 2013)
The UK government is part-way through significant cuts in spending on public services as it attempts to deal with the large hole in the UK's public finances. As part of this, grants from the UK Treasury to the Welsh Government have been reduced in real terms each year since 2009-10, and the spending plans set out by the Treasury have confirmed further cuts in 2014-15 and 2015-16. Furthermore, with further fiscal tightening planned in the two years after that, grants to the Welsh Government look set to continue to fall in real terms in 2016-17 and 2017-18. If delivered, this would mean an unprecedented seven years of retrenchment in public service spending in Wales, in stark contrast to the first ten years of devolution, when the Welsh Government enjoyed substantial year-on-year real-terms spending increases. This report sets out the current UK economic fiscal context and explores the implications for Wales. In particular, it examines the changes in Welsh Government spending in recent years, and sets out a number of scenarios for the Welsh Government's budget for the period to 2025. It also explores the trade-offs facing the Welsh Government when setting its departmental budgets, and relates these to the spending pressures that will be faced in the coming decade as the impact of demographic change begins to make itself felt.
Keywords: 330